IDENTIFIKASI RHODAMIN-B DALAM LIPTINT YANG BEREDAR DI MAHASISWI FARMASI UNIVERSITAS MUHAMMADIYAH GRESIK - Purwanto, Hepfriya Nur Rachma; Harahap, Hotma Wardhani (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2025)
Good cosmetics are cosmetics that do not contain ingredients harmful to the skin or other body health, such as rhodamin-B dye. Lipstick is the most widely used decorative cosmetic product, one type of lipstick is lip tint.According to the Regulation of the Head of the POM RI Agency No.18 of 2015 concerning Technical Requirements for Cosmetic Materials, prohibited dyes include Red K3 and K10 dyes (Rhodamin-B) but are widely misused in lipsticks. Rhodamin-B is a synthetic dye used in the textile and paper industry.Rhodamin-B is harmful to the body due to its chemical properties and contains heavy metals, for example such as chlorine and alkylating compounds. Based on preliminary studies that have been carried out, as many as 33.33% of Pharmacy Students of the University of Muhammadiyah Gresik used lip tint and there were four lip tint samples that were tested. Based on the results of three types of qualitative tests, namely Rhodamin-B kits, thin layer chromatography and lip tint sample staining tests, it was concluded that there was no rhodamin-B hazardous material content in the four circulating samples.